Genomic Islands as a Marker to Differentiate between Clinical and Environmental Burkholderia pseudomallei - Bartpho, Thanatchaporn; Wongsurawat, Thidathip; Wongratanacheewin, Surasakdi; Talaat, Adel M.; Karoonuthaisiri, Nitsara; Sermswan, Rasana W. (PLOS ONE, 2012)
Burkholderia pseudomallei, as a saprophytic bacterium that can cause a severe sepsis disease named melioidosis, has preserved several extra genes in its genome for survival. The sequenced genome of the organism showed high diversity contributed mainly from genomic islands (GIs). Comparative genome hybridization (CGH) of 3 clinical and 2 environmental isolates, using whole genome microarrays based on B. pseudomallei K96243 genes, revealed a difference in the presence of genomic islands between clinical and environmental isolates. The largest GI, GI8, of B. pseudomallei was observed as a 2 sub-GI named GIs8.1 and 8.2 with distinguishable %GC content and unequal presence in the genome. GIs8.1, 8.2 and 15 were found to be more common in clinical isolates. A new GI, GI16c, was detected on chromosome 2. Presences of GIs8.1, 8.2, 15 and 16c were evaluated in 70 environmental and 64 clinical isolates using PCR assays. A combination of GIs8.1 and 16c (positivity of either GI) was detected in 70% of clinical isolates and 11.4% of environmental isolates (P<0.001). Using BALB/c mice model, no significant difference of time to mortality was observed between K96243 isolate and three isolates without GIs under evaluation (P>0.05). Some virulence genes located in the absent GIs and the difference of GIs seems to contribute less to bacterial virulence. The PCR detection of 2 GIs could be used as a cost effective and rapid tool to detect potentially virulent isolates that were contaminated in soil.